The Influence of Private Actors on the Education of Teachers in Sweden. A Networked Ethnography Study of Education Policy Mobility - Player-Koro, Catarina; Beach, Dennis (Acta Paedagogica Vilnensia, 2017)
Policy networks constitute a new form of education governance through a mix of jodint working arrangements involving both public and private sector actors. This article explores the work of a specific actor in a Swedish educational policy network, active in the digitalization of schools. We examine how this actor fits within global policy networks and activities that are adding to and profiting from problems of the educational sector and not providing solutions for these difficulties by exploiting the existing mediatized problems in order to motivate the reduced expenditure on state-owned public services and to develop a conceptual foundation for launching private alternatives.
Keywords: Network Ethnography; Education Politics; Commodification; Policy network